An exploration of mammographers' attitudes towards the use of social media for providing breast screening information to clients. Issue 3 (August 2017) - Scragg, B.; Shaikh, S.; Shires, G.; Stein Hodgins, J.; Mercer, C.; Robinson, L.; Wray, J.
Abstract: Introduction: Increasingly patients and clients of health services are using social media to locate information about medical procedures and outcomes. There is increasing pressure for health professionals to engage in on-line spaces to provide clear and accurate information to their patient community. Research suggests there are some anxieties on the part of practitioners to do this. This study aimed to explore the attitudes of the NHS breast screening programme workforce towards engaging in online discussions with clients about breast screening. Method: 78 practitioners, representing a range of professional roles within the NHS Breast Screening Programme, attended one of 4 workshops. We used a Nominal Group Technique to identify and rank responses to the question: " What are the challenges that practitioners face in using SoME as part of their role?" Responses were categorised into themes. Participants were also asked to identify solutions to these challenges. Results: Challenges : We identified two overarching themes: (1) Working within boundaries : which was further categorised into (a) Professional/legal accountability; (b) Information accuracy and (c)Time as a boundary, and (2) Support : further categorised into (a) Employer and (b) Manager.Solutions: These included: training in technical and interactional aspects of on-line communication and a responsibility to better understand employer and professional body SoMe policies. Conclusion: The study participants appeared willing and motivated to engage in SoMe. However, in keeping with the literature from other disciplines, a number of challenges need to be overcome for its use to be adopted more widely by breast screening professionals. Highlights: Breast screening professionals appeared willing and motivated to engage in SoMe. They saw the benefit of SoMe for their clients. They saw the benefit of SoMe for professional networking and development. Professionals felt confused and unsupported by SoMe communication policies. Professionals asked for training to support online communication with clients.